The Fading of Philosophy - Gianni Vattimo (EJP import test, 2017)
Summary: Psycho-analysis emerged as the science of modern man within the decline of metaphysics, the limitation of philosophy’s claims to immutable knowledge. Established by Plato as speculation upon eternal structures, followed by the subjectification of truth in Christianity, Kant, and Romanticism, philosophy became with Heidegger a knowledge of the event situated within contingency and history. As metaphysical imperiousness fades, psychoanalysis is recognized as an historical project, invoking a new understanding of truth and bringing up questions about friendship, charity, health and salvation.[1]
Keywords: Friendship; Health; historicity; Knowledge Domains; Metaphysical Imperiousness; salvation